Experiments with Book Festival People (Real and Imaginary) - Driscoll, Beth; Squires, Claire (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2020)
While there are multiple approaches to researching cultural events, predominant academic frames tend to be either sociological or situated within a creative industries discourse. Neither of these approaches have supported sustained engagement with individual, interior experience at book festivals. Creative writers have imaginatively depicted these sites of author-reader interaction, and developing scholarship focuses on autoethnography and the phenomenological. In this article, we extend and materialise these approaches through a series of creative, arts-informed interventions: @AuthorsYurt, a personification on Twitter of the Edinburgh International Book Festival’s green room; Paper Dolls, a series of cut-out-and-dress dolls depicting audience members at a variety of book festivals across Europe, North America and Australia; and ClueButeDo, a satirical reworking of the audience feedback form at a small island crime festival in the UK. Each of the three experiments reveals aspects of personhood at book festivals, engaging with ideas of interiority, individuality, and experientiality, as well as of inclusion and exclusion. In pursuing this aim, we are guided by the autoethnographic slogan, “No Insight Without Inside, No Inside Without Outside” (Nunu Otot).